Laparoscopic versus open management of duodenal perforation: a comparative study at a District General Hospital - Motewar, Ashish; Tilak, Mandar; Patil, Deepak; Bhamare, Nikhil; Bhople, Laxmikant (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction: Duodenal perforation is one of the common pathologies in patients presenting in emergency with acute abdominal pain in an emergency ward and requires prompt surgery as life saving and curative intervention. The present study was conducted to determine whether the minimal access approach by laparoscopy was equally feasible as the open method. Aim: To compare laparoscopic vs. open management duodenal perforation in all aspects. Material and methods : Inclusion criteria: patients presenting to the emergency ward with acute pain in the abdomen with clinical signs of peritonitis and air under the diaphragm on X-ray abdomen standing were selected. Exclusion criteria were: patient age 70 years, presentation > 2 days, shock with systolic blood pressure < 90 mm Hg which did not improve after hydration with 2000 ml of Ringer lactate solution, respiratory distress, history of cardiac disorder or respiratory disorders such as ischemic heart disease, arrhythmias, chronic obstructive pulmonary disease or asthma, bleeding and clotting disorders, pregnancy in females, previous upper abdominal surgery, and intra-operatively patients having perforation other than duodenal perforation. After excluding patients fitting the above criteria, two groups – test and control – were formed. Results : We found that complications both early and late were significantly fewer in patients treated by laparoscopy. Thus laparoscopy was both feasible and had comparable mortality and leakage rate. Conclusions : Laparoscopic management of perforated duodenal ulcer is feasible, effective and decreases morbidity and overall treatment time and cost if performed in properly selected patients.